THE CRIME OF BRIBERY BETWEEN SHARIA AND LAW - Dr, Laith Ali Khalil Al-Junaih (American Journals Publishing, 2025)
The crime of bribery is considered one of the most serious crimes of corruption and among the crimes that have negative effects on society. The Iraqi state has sought to combat the crime of bribery through various mechanisms, legal legislation and anti-corruption bodies, but despite that, society has not been spared from this crime. It is necessary to combine efforts and all actors and the presence of a real political administration to combat this crime.
Keywords: Bribery crime, corruption, anti-bribery.